2020
DOI: 10.1182/bloodadvances.2020002175
|View full text |Cite
|
Sign up to set email alerts
|

RAS/CBL mutations predict resistance to JAK inhibitors in myelofibrosis and are associated with poor prognostic features

Abstract: The dysregulation of the JAK/STAT pathway drives the pathogenesis of myelofibrosis (MF). Recently, several JAK inhibitors (JAKis) have been developed for treating MF. Select mutations (MTs) have been associated with impaired outcomes and are currently incorporated in molecularly annotated prognostic models. Mutations of RAS/MAPK pathway genes are frequently reported in cancer and at low frequencies in MF. In this study, we investigated the phenotypic, prognostic, and therapeutic implications of NRASMTs, KRASMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 44 publications
2
54
0
Order By: Relevance
“…In the current study, we identified RAS mutations and complex karyotype as independent predictors of poor response to Ven + HMA while no associations with IDH1/2 mutations were apparent; incidentally, the association between poor response and preleukemic PV phenotype was explained by the latter clustering with complex karyotype. Interestingly, we have recently identified RAS / CBL mutations as predictors of poor treatment response to ruxolitinib, in patients with myelofibrosis 23 . In a previous study of relapsed/refractory AML in older patients, IDH2 and NPM1 mutations were associated with higher response rates and durable remissions while an association with IDH1 was less certain 24 .…”
Section: Discussionmentioning
confidence: 92%
“…In the current study, we identified RAS mutations and complex karyotype as independent predictors of poor response to Ven + HMA while no associations with IDH1/2 mutations were apparent; incidentally, the association between poor response and preleukemic PV phenotype was explained by the latter clustering with complex karyotype. Interestingly, we have recently identified RAS / CBL mutations as predictors of poor treatment response to ruxolitinib, in patients with myelofibrosis 23 . In a previous study of relapsed/refractory AML in older patients, IDH2 and NPM1 mutations were associated with higher response rates and durable remissions while an association with IDH1 was less certain 24 .…”
Section: Discussionmentioning
confidence: 92%
“…There is evidence to support alternative heterodimer formation between JAK2 and JAK1 or TYK1 in MPN cell line models persistently exposed to ruxolitinib and evidence to support recruitment of alternative MAPK signalling bypassing the JAK/STAT pathway as mechanistic explanations of this resistance [ 150 ]. The complexity of the genetic changes within the MPN clone may also determine the responsiveness of the cell to ruxolitinib, whilst new somatic mutations driving clonal evolution on therapy and subsequent expansion of new clones has been clearly documented [ 151 , 152 ].…”
Section: Targeted Therapymentioning
confidence: 99%
“… [ 54 , 60 , 108 , 119–121 ] CBL Mutations lead to increased STAT5 phosphorylation, cytokine hypersensitivity and cell proliferation; mostly homozygous missense substitutions. <1 0–2 0–6 4 Reduced overall survival in MF, resistance to JAKi [ 60 , 108 , 122 , 123 ] NRAS/KRAS Heterozygous missense mutations, particularly in codons 12, 13 and 61 led to a constitutive activation of growth signalling. <1 <1 3–4 7–15 Reduced overall survival in MF, resistance to JAKi [ 60 , 108 , 123 , 124 ] PTPN11 Missense mutations in Src-homology 2 (N-SH2) and phosphotyrosine phosphatase (PTP) domains <1 <1 1 2–5 Reduced overall survival in BP [ 108 ] Transcription factors RUNX1 Element of core bonding factor (CBF) heterodimer.…”
Section: Mutational Landscape Of Mpnmentioning
confidence: 99%